2019
DOI: 10.3389/fphar.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Da-Bu-Yin-Wan and Qian-Zheng-San Ameliorate Mitochondrial Dynamics in the Parkinson’s Disease Cell Model Induced by MPP+

Abstract: To investigate the effect of Da-Bu-Yin-Wan and Qian-Zheng-San (DBYW and QZS) on mitochondrial mass in Parkinson’s disease (PD) cell model induced by 1-Methyl-4-phenylpyridinium Ion (MPP + ). The SH-SY5Y cell was selected and treated with MPP + . The PD model was intervened with DBYW and QZS. CCK-8 method was used to detect the survival rate of cells in each group. Mitochondria was labeled by mitoTracker ® Red CMXRos probe and observed by lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…We found that BYQZF rescued MPP + -induced mitochondrial alterations, including ΔΨm and ATP levels in the negative treatment group, consistent with a previous study (Gai et al, 2019). However, BYQZF did not rescue mitochondrial dysfunction in MPP + -induced SH-SY5Y cells transfected with the parkin-knockdown plasmid.…”
Section: Discussionsupporting
confidence: 91%
“…We found that BYQZF rescued MPP + -induced mitochondrial alterations, including ΔΨm and ATP levels in the negative treatment group, consistent with a previous study (Gai et al, 2019). However, BYQZF did not rescue mitochondrial dysfunction in MPP + -induced SH-SY5Y cells transfected with the parkin-knockdown plasmid.…”
Section: Discussionsupporting
confidence: 91%
“…The protective effects of BYQZF on mitochondrial function have been confirmed in in vitro and in vivo studies (Zhang et al, 2013;Zhang et al, 2018;Gai et al, 2019); parkin was found to play an important role in this process. However, the mechanisms by which BYQZF ameliorates mitochondrial dysfunction via parkin are unclear.…”
Section: Discussionmentioning
confidence: 75%
“…Our previous studies showed that Da-Bu-Yin-Wan ameliorates MPTP-induced behavioral impairment, increases the expression of tyrosine hydroxylase in the substantia nigra, and prevents loss of substantia nigra dopaminergic neurons in a PD mouse model (Gong et al, 2014). Moreover, Da-Bu-Yin-Wan and/or Qian-Zheng-San significantly increase ATP levels and complex I activity in the midbrain tissue of PD model mice (Zhang et al, 2013), and BYQZF reduced mitochondrial damage and improved the mitochondrial morphological structure in a cellular model of PD (Zhang et al, 2018;Gai et al, 2019). These studies suggest that BYQZF had neuroprotective effects on mitochondrial function and may be applicable as a mitochondrion-targeted therapeutic drug for treating PD.…”
Section: Introductionmentioning
confidence: 99%
“…With the extensive use of acupuncture as an ASM therapy for PD, the mechanisms based on animal model of acupuncture treatment for PD were widely investigated. 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), 1-methyl-4-phenylpyridinium (MPP+), 6-hydroxydopamine (6-OHDA) and rotenone are widely used as inducers in animal models of PD (Andrzejewski et al, 2019; Gai et al, 2019; He et al, 2019).…”
Section: Parkinson’s Diseasementioning
confidence: 99%